Penerapan Laundry Management System Web-Mobile Menggunakan Metode Waterfall dengan Evaluasi TAM dan Blackbox Testing - Pangesty, Shandika Sayyid Ammar; Wibowo, Adityo Permana (TIN: Terapan Informatika Nusantara, 2025)
The main problems faced by Mulia Laundry stem from business processes that are still carried out manually, including service recording, inventory management, and customer transactions. This situation reduces operational efficiency, increases the possibility of recording errors, and hinders service speed. Therefore, the purpose of this study is to develop and implement a web- mobile based Laundry Management System that can automate the entire laundry business process to be more efficient, accurate, and integrated. The system is designed using a client-server architecture through REST API, with a structured software engineering approach through Unified Modeling Language (UML) modeling and using the Waterfall model Software Development Life Cycle (SDLC) development method. The main features of this system include customer management, services, inventory, transactions, and real-time order status tracking. The system was evaluated using Blackbox Testing, which showed that all features operated according to specifications without any errors in the main application processes. In addition, user acceptance testing using the Technology Acceptance Model (TAM) obtained an average perceived usefulness (PU) score of 4.67 and a perceived ease of use (PEOU) score of 4.47, both of which are in the excellent category. The results of this study indicate that the system is well accepted by users and can prove its effectiveness in improving operational efficiency and supporting the digitization of business processes in laundry MSMEs.